PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN KUALITAS SDM TERHADAP KINERJA PERSONEL SATUAN LALU LINTAS POLRES PAMEKASAN - jurnalmap map; Muamar Amin; Nugroho Mawardi Wibowo; Muninghar ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at the Pamekasan Regional Police Station. with a total sample of 85 people. The objectives of this study are 1) To describe how the transformational leadership, work motivation, and quality of human resources on the performance, 2) To find out and analyze whether transformational leadership, work motivation and quality of human resources simultaneously have a significant influence on the performance, 3) To find out and analyze whether transformational leadership, work motivation and quality of human resources partially have a significant influence on the performance. Analysis of data using SPSS. The results of the study show that 1). Simultaneously, transformational leadership, work motivation, HR quality have a very significant effect on personnel performance 2). Partially, transformational leadership, work motivation and quality of human resources have a significant effect on the performance. Keywords: Transformational Leadership, Work Motivation, The quality of human resources and the performance of Personnel.